2007
DOI: 10.1002/pca.1000
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroids from the medicinal fern Microsorum scolopendria (Burm. f.)

Abstract: Fronds of the fern Microsorum scolopendria are widely used in traditional medicine in the Society Islands. They were investigated for the presence of ecdysteroids, which might be responsible for at least some of their medicinal properties. M. scolopendria represents an excellent source of ecdysone (0.16% of dry weight) and 20-hydroxyecdysone (0.20%), and also contains significant amounts (0.01-0.02%) of makisterones A and C, inokosterone and amarasterone A, together with lower amounts of poststerone and of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Some reference ecdysteroids were isolated in the laboratory from various plants: MaA, from Ajuga iva [16]; 20dMaA from the fern Microsorum scolopendria [17]. 24epiMaA was prepared by chemical reduction of 24,28-dehydromakisterone A [7].…”
Section: Chemicalsmentioning
confidence: 99%
“…Some reference ecdysteroids were isolated in the laboratory from various plants: MaA, from Ajuga iva [16]; 20dMaA from the fern Microsorum scolopendria [17]. 24epiMaA was prepared by chemical reduction of 24,28-dehydromakisterone A [7].…”
Section: Chemicalsmentioning
confidence: 99%
“…Some of these species show a very similar morphology, especially M. scolopendria and M. rubidium, which may induce confusion when collecting them for medicinal preparation purposes. Biologically active compounds belonging to the ecdysteroid family have been found in the genus Polypodium [6][7][8], and a phytochemical study of M. scolopendria revealed the presence of high amounts of ecdysteroids [9]. Ecdysteroids are known to have many pharmacological effects in mammals/humans, e.g.…”
mentioning
confidence: 99%
“…Comparison of the 13 C NMR (Table 2) and DEPT spectra with those of 6 showed that the oxyquaternary carbon for C-20 in 6 was replaced by a methine (d C 41.8) in 4. These findings indicated that the aglycone of 4 was 25-deoxyecdysone (Snogan et al, 2007). The sugar part was also indicated to be a b-D-glucopyranosyl group by the 1 H and 13 C NMR spectroscopic data and acid hydrolysis, and it was bound to C-3 via a glycosidic linkage as deduced from correlations in the HMBC and NOESY spectra.…”
Section: Resultsmentioning
confidence: 87%